2008
DOI: 10.1007/s11270-008-9635-x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Microcystin LR and LW on Suspended Particulate Matter (SPM) at Different pH

Abstract: The occurrence of microcystins (MC) during aquatic blooms of cyanobacteria in eutrophicated freshwater body has increasingly become an environmental and health concern worldwide. An experimental study was conducted to investigate the adsorption of two common variants of microcystins, MCLR and MCLW, onto SPM at different pH values. The results showed that most microcystins spiked into an SPM solution with the concentration of 0.25g/l was adsorbed onto solids at pH3 (>95%) and 7 (>85%).At pH13, the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 33 publications
(47 reference statements)
0
25
0
Order By: Relevance
“…On the other hand, it is known that some cyanotoxins, such as microcystins, can be adsorbed by suspended particles in the water-such as organic detritus- (Morris et al 2000;Liu et al 2008), becoming an additional exposure or immobilization pathway. In the present study, the collected water was filtered, evaluating thereby only the toxicity of water-soluble substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is known that some cyanotoxins, such as microcystins, can be adsorbed by suspended particles in the water-such as organic detritus- (Morris et al 2000;Liu et al 2008), becoming an additional exposure or immobilization pathway. In the present study, the collected water was filtered, evaluating thereby only the toxicity of water-soluble substances.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity assessment of purified cyanotoxins might not reflect at all the events occurring in the environment, as it has been demonstrated that their toxicity is susceptible to be modified when they are associated to other molecules (Liu et al 2008). Hence, a better option would be to make assessments with crude extracts, evaluating the toxic effects of the different cellular components after blooms have occurred in natural environments (Sotero-Santos et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the full-scale trial, there would also have been a significantly higher loading of sediment than in the laboratory trials, where wastewater was collected from the surface of ponds. Adsorption by sediments, and subsequent biodegradation, may have accelerated the reduction of microcystins in the full-scale trial compared to the laboratory trials (Harada and Tsuji, 1998;Liu et al, 2008). Biodegradation, UV radiation and adsorption may all have played a role in the longer term reduction of microcystins from the dissolved phase, and may have accelerated their reduction compared to the smaller scale trials under controlled laboratory conditions.…”
Section: Microcystins Dynamicsmentioning
confidence: 99%
“…The ionizable groups (two carboxyls and one guanidino) of MCLR can be deprotonated or protonated to make MCLR positive or negative at different pH values, respectively. According to the pKa values of MCLR (pKa 1 , 2.09; pKa 2 , 2.19; pKa 3 , 12.48) (Liu et al 2008), the mass fractions of MCLR species can be calculated as follows:…”
Section: Adsorption Isotherms and Thermodynamicsmentioning
confidence: 99%